2007
DOI: 10.1111/j.1439-0264.2007.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of the Sheep’s Cervical Spine Segment 3/4 – A Histomorphological and Histomorphometrical Study

Abstract: The 2-year-old sheep is a frequently used model in spinal orthopaedic research; however, so far no investigations have been performed on physiological tissue of untreated animals. In this study, the cervical spine segment 3/4 of eight 2-year-old female Merino sheep was evaluated histologically and histomorphometrically. Specimens were stained with Masson-Goldner-Trichrome, Safranin-Orange/Lightgreen, Safranin-Orange/von Kossa and Astrablue. Analysis of bone mass, mass of cartilage and mineralized cartilage in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, it is the first time that clear on/off markers were identified that allows to distinguish the three different cell types of the IVD tissue. Bovine and ovine IVDs resemble human IVDs by the occurrence of notochordal cells with a few cells at birth which decrease rapidly with maturity 32 38 39 . Here, notochordal cells seemed to be absent or at a low number for both age-groups as no cells with notochordal cell morphology were observed in NP tissues ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is the first time that clear on/off markers were identified that allows to distinguish the three different cell types of the IVD tissue. Bovine and ovine IVDs resemble human IVDs by the occurrence of notochordal cells with a few cells at birth which decrease rapidly with maturity 32 38 39 . Here, notochordal cells seemed to be absent or at a low number for both age-groups as no cells with notochordal cell morphology were observed in NP tissues ( Fig.…”
Section: Discussionmentioning
confidence: 99%